PENGARUH CAPITAL ADEQUACY RATIO DAN NON PERFORMING LOAN TERHADAP PROFITABILITAS MELALUI LOAN TO DEPOSIT RATIO - Putri Junianti; Nugroho Mardi Wibowo; C. Sri Hartati (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2023)
The purpose of this study is to describe and analyze the effect of CAR and NPL on the profitability of conventional banking companies listed on the Indonesia Stock Exchange that are intervened by LDR. This study uses a type of quantitative research. All conventional banks listed on the Indonesia Stock Exchange from 2017 to 2021 as a study population are 37 banks. The sampling technique in this study used purposive sampling, so that 13 companies were determined as samples. This study uses the PLS data analysis method with the help of the SmartPLS 3.0 program. The results showed that the Capital Adequacy Ratio had a negative and insignificant effect on the company's Loan To Deposit Ratio. Non Performing Loans have a negative and significant effect on the company's Loan To Deposit Ratio. Capital Adequacy Ratio and Non-Performing Loans have a positive and not significant effect on company profitability. Loan To Deposit Ratio and Non Performing Loan have no significant negative effect on Profitability through Loan To Deposit Ratio conventional banking companies listed on the Indonesia Stock Exchange.